The Effect of Financial Ratios and Revenue Growth on Stock Returns in Manufacturing Companies on the Indonesia Stock Exchange - Mohamad Arik; Riyanto Setiawan Suharsono; Moh Halim (West Science Accounting and Finance, 2024)
Investment is the investment of assets or funds with the aim of obtaining profits in the future. This investment can be made in the capital market. The capital market is a place where securities are traded. This study aims to find out whether liquidity, profitability, leverage, market and revenue growth affect stock returns in manufacturing companies listed on the IDX. The theory used is signal theory, using a type of descriptive approach using the population in this study are manufacturing sub-sector companies listed on the Indonesia Stock Exchange. The total population in this study is 209 companies. This study produced: Liquidity ratio has no effect on stock retrun, Profitability ratio has no effect on stock returns, Leverage ratio has no effect on stock returns, Market ratio has no effect on stock retuns, Income has no effect on stock returns.